Hydrogen recycling during RF plasma heating in the U-3M torsatron - Pashnev, V.K.; Petrushenya, A.A.; Ponomarenko, N.P.; Sorokovoy, E.L. (Вопросы атомной науки и техники, 2014)
The hydrogen recycling behavior has been studied during the plasma experiments in torsatron U-3M. For this purpose, the time dependence of the molecular hydrogen pressure in the U-3M torsatron vacuum chamber in the modes of RF wall conditioning and RF plasma heating has been measured. The experimental results show that the hydrogen pumping from the vacuum chamber runs at constant rate during the RF discharge for each mode. After RF power switching-off the inverse desorption of hydrogen, accumulated during the RF discharge in the vacuum chamber walls and helical coil surfaces, is observed. When the antenna anode voltages and the RF pulse duration in both modes are increasing, the character of the time dependences of hydrogen pressure does not change significantly.